Means in the individuals’ study: the microanalysis as pomp to analyse trajectories - Alves, Jessica Santana de Assis (Temporalidades, 2019)
Inside the field of the history the study of the life of an individual can be carried out by multiple perspectives, where the biographical method stands out in this meander. However, in this article we look to carry out reflections on the approach of microanalytical inquiry, detaching the aspects that are wrapped in one of the objects of study of the micro-historian: the Trajectory. Our preoccupation is to realize: Of what does it sort the micro-history out does it present itself an alternative appropriated to investigate individuals’ trajectories? In way to understand the approach as applicable analytical instrument to the historical study of determined reality, to expose his approaches and the challenges - metodológicos that surround it.